2012
DOI: 10.1038/aps.2011.202
|View full text |Cite
|
Sign up to set email alerts
|

Retinol induces morphological alterations and proliferative focus formation through free radical-mediated activation of multiple signaling pathways

Abstract: Aim: Toxicity of retinol (vitamin A) has been previously associated with apoptosis and/or cell malignant transformation. Thus, we investigated the pathways involved in the induction of proliferation, deformation and proliferative focus formation by retinol in cultured Sertoli cells of rats. Methods: Sertoli cells were isolated from immature rats and cultured. The cells were subjected to a 24-h treatment with different concentrations of retinol. Parameters of oxidative stress and cytotoxicity were analyzed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Previous studies suggest that retinol may enhance free radical production, leading to phosphorylation of Src-tyrosine kinase, MAPK/ERK kinases 1/2 (MEK1/2), cAMP-responsive element binding protein (CREB), and extracellular signal-regulated kinases 1 and 2 (ERK1/2). The activation of this pathway appears to be involved in the onset of some of the deleterious effects, such as malignant transformation and cell proliferation (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that retinol may enhance free radical production, leading to phosphorylation of Src-tyrosine kinase, MAPK/ERK kinases 1/2 (MEK1/2), cAMP-responsive element binding protein (CREB), and extracellular signal-regulated kinases 1 and 2 (ERK1/2). The activation of this pathway appears to be involved in the onset of some of the deleterious effects, such as malignant transformation and cell proliferation (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that nongenomic actions can influence brain functioning, affecting synaptic transmission, catecholamine production in the brain, cell‐cycle regulation mediated by mitogen‐activated protein kinase (MAPK), protein kinase B (PKB), and protein kinase C activation . However, it was recently demonstrated that retinol‐induced ROS production in Sertoli cells is able to activate different pathways of protein kinases, including MAPKs, extracellular‐signal‐regulated kinases (ERK1/2), c‐Jun N‐terminal kinases, and PKB . Thus, the oxidative stress observed in the brain of middle‐aged Wistar rats after the chronic supplementation of moderate amounts of vitamin A may also have a deleterious effect upon important cell signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effect of retinol on oxidative stress remains controversial. [35][36][37] However, STRA6, the receptor for retinoic acid uptake, induces mitochondrial depolarization and intracellular ROS. 19,38 In the present study, treatment with ME increased the mRNA and protein levels of STRA6 and increased intracellular ROS levels via mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%